A cluster-based network architecture scheme for QoS improvement in WLAN. (2017) - Vignesh, N. Arun; Poongodi, P.
The crucial issues in the wireless LAN are low coverage range and high mobility. The consequences are less number of users due to the low coverage range and inferior network performance due to high mobility. To overcome the above issues a new architecture known as cluster-based network architecture (CBNA) is proposed. CBNA scheme assigns a node to one of the many layers and creates a cluster head for each layer. The cluster head can manage the mobility of wireless mobile nodes. Layering helps increase the number of users. Experimental results evaluate the CBNA by varying the position of the destination node. Simulation results have shown that the proposed (CBNA) scheme increases the overall network performance in the different stages that was analysed using the quality of service parameters such as packet delivery ratio, drop rate, throughput, delay, network efficiency and overhead ratio.